2012
DOI: 10.1371/journal.pone.0031943
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to DDT and Pyrethroids and Increased kdr Mutation Frequency in An. gambiae after the Implementation of Permethrin-Treated Nets in Senegal

Abstract: IntroductionThe aim of this study was to evaluate the susceptibility to insecticides of An. gambiae mosquitoes sampled in Dielmo (Senegal), in 2010, 2 years after the implementation of Long Lasting Insecticide-treated Nets (LLINs) and to report the evolution of kdr mutation frequency from 2006 to 2010.MethodsWHO bioassay susceptibility tests to 6 insecticides were performed on adults F0, issuing from immature stages of An. gambiae s.l., sampled in August 2010. Species and molecular forms as well as the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Similar observations have been made in Niger, Equatorial Guinea (Bioko) and Kenya (Stump et al ., 2004;Sharp et al ., 2007;Czeher et al ., 2008). Recent studies in Senegal and Liberia have also demonstrated increased frequencies of pyrethroid resistance after high LLIN usage (Ndiath et al ., 2012;Temu et al ., 2013). The rapid rise of pyrethroid resistance in Muleba also coincides with the intensive use of IRS in the district (since 2007) for the control of malaria transmission and was recorded a few years earlier in the neighbouring country of Uganda (Protopopoff et al ., 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Similar observations have been made in Niger, Equatorial Guinea (Bioko) and Kenya (Stump et al ., 2004;Sharp et al ., 2007;Czeher et al ., 2008). Recent studies in Senegal and Liberia have also demonstrated increased frequencies of pyrethroid resistance after high LLIN usage (Ndiath et al ., 2012;Temu et al ., 2013). The rapid rise of pyrethroid resistance in Muleba also coincides with the intensive use of IRS in the district (since 2007) for the control of malaria transmission and was recorded a few years earlier in the neighbouring country of Uganda (Protopopoff et al ., 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the frequency of alleles associated with pyrethroid resistance have been shown to change in response to increasing ITN coverage [31, 33, 34], although the association of phenotypic resistance with increasing ITN coverage has been less well documented. Given enough time, the effect of ITNs on phenotypic resistance may occur even at lower levels of coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the kdr frequency in Anopheles populations in Dielmo can reach 47% [12, 33] and may increase significantly after inter-generational crosses.…”
Section: Methodsmentioning
confidence: 99%